Using direct benefit transfers to transfer benefits to women: a perspective from India. Issue 8 (17th November 2019) - Sabherwal, Rashi; Sharma, Devesh; Trivedi, Neeraj
ABSTRACT: Enabling women to have control over their entitled incomes from direct benefit transfers (DBTs) can strengthen their bargaining power and transform their banking activity, mobility, and other key outcomes. However, ensuring that women are able to effectively access these benefit transfers in an enabling environment where DBTs can lead to transformative impacts requires recognising the economic, normative, and social barriers that women face in accessing and controlling their accounts. It also requires an understanding of the incentives of financial services providers and their constraints in adapting to and addressing these barriers. This article addresses these and offers recommendations for policymakers and practitioners as they seek to improve women's financial inclusion and fully harness the potential of benefit transfers in empowering women economically and socially.